2019
DOI: 10.3390/f10110940
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Tolerance in Fraxinus angustifolia Vahl.: Seed Emergence in Field and Germination Trials

Abstract: The effect of salinity on seed germination/emergence in narrow-leaved ash (Fraxinus angustifolia) was studied both under field and laboratory conditions, in order to detect critical values to NaCl exposure. Research Highlights: Novel statistical methods in germination ecology has been applied (i) to determine the effects of chilling length and salinity (up to 150 mM NaCl) on Fraxinus angustifolia subsp. oxycarpa seed emergence, and (ii) to estimate threshold limits treating germination response to salinity as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
2
1
0
Order By: Relevance
“…We showed that both seedlings and callus of ash are able to develop during slight/medium (not exceeding 0.5% or 1.0%) salt stress. Our results are in agreement with Raddi et al [60] who showed that F. angustifolia (Vahl.) is able to germinate at low salinity and to tolerate temporarily moderate salinity (not exceeding 75 mM NaCl) conditions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We showed that both seedlings and callus of ash are able to develop during slight/medium (not exceeding 0.5% or 1.0%) salt stress. Our results are in agreement with Raddi et al [60] who showed that F. angustifolia (Vahl.) is able to germinate at low salinity and to tolerate temporarily moderate salinity (not exceeding 75 mM NaCl) conditions.…”
Section: Discussionsupporting
confidence: 94%
“…Ultimately, the plant becomes resistant to abiotic factors [63,64]. Under environmental stress, photorespiration acts as an energy sink, preventing excessive reduction of the photosynthetic electron transport chain and photoinhibition, as well as preventing the accumulation of ROS [60,65]. Peroxidases in general are involved in multiple metabolic processes during the entire life cycle of plants, including the metabolism of ROS, reactive nitrogen species (RNS) and metabolism of phytohormones (e.g., auxins), as well as in the production of lignin and suberin, and in cross-linking of cell wall components [41,42,66].…”
Section: Discussionmentioning
confidence: 99%
“…However, the percent survival under this treatment was considerably low compared to other treatments. This response is the same as in the numerous plant species affected by salinity stress during germination (e.g., Katembe et al 1998;Ghazy et al 2009;Liu et al 2010;Raddi et al 2019). In the study of Fang et al (2006), there was a significant reduction in the seedling survival with increase in NaCl concentration after 50 days of treatment.…”
Section: Discussionsupporting
confidence: 64%